(untitled) (Fiep Bulletin - online, 2012)
Golf has become more popular over the years. You can notice this growth mainly in the number of senior players, which contrasts with the other sports. This quantitive, exploratory, experimental and transversal study aims the identification of the main hindrances that limit the massification of Golf, as well as the pertinence of the choices offered by schools in the greater Oporto area. The non random sample consists of 26 Physical Education teachers (42.3% female and 57.7% male), from 26 schools in the greater Oporto area. Of these schools, only 9 (34.6%) have Golf as a School Sport. The remaining 17 schools (65.4%) do not offer Golf as a possible choice. The average age of the teachers questioned is 45.31 years and the standard deviation is 7.3. In the statistical process, we used the IBM SPSS Statistics 19 software, we recorded the descriptive statistics, the frequency tables and conducted statistical tests, namely the t Test and Factor Analysis. We observe that the offer of Golf as a School Sport is limited and that the level of acceptance of this sport is lower than of other School Sports, even though the students are globally successful in learning it. The hindrances found are: the technicalities, the human resources, the difficult access to Golf courses, the lack of training facilities and the individual results as well as the cost of the equipment.